Leadership is very important to improve a community group as like the fish farmer group in KUIH Telaga Biru, Desa Parigi Mekar, Ciseeng, Bogor. The research in focuses on how principal, commitment and a figure of group's leader, and the style of the leadership. From the research, it has been the shown that group's leader use the leadership principal of Muhammad SAW as like sidiq, tab/igh, amanah, dan fathonah. Group's leader regard their members as a leader, and the group's l - Anna Fatchiya (Buletin Ekonomi Perikanan, 2007)
Leadership is very important to improve a community group as like the fish farmer group in KUIH Telaga Biru, Desa Parigi Mekar, Ciseeng, Bogor. The research in focuses on how principal, commitment and a figure of group's leader, and the style of the leadership. From the research, it has been the shown that group's leader use the leadership principal of Muhammad SAW as like sidiq, tab/igh, amanah, dan fathonah. Group's leader regard their members as a leader, and the group's leader was a model leader to group members, also he have huge commitment in the interest of the group.